Pengaruh Intellectual Capital, Kebijakan Dividen, dan Pertumbuhan Aset terhadap Kinerja Perusahaan dengan Komite Audit sebagai Variabel Moderasi - Pattiselanno, Vanezha Wilhelmina; Widiyati, Dian (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
This study aims to determine the influence of intellectual capital, dividend policy, and asset growth on company performance with the audit committee as a coding variable in Primary Consumer companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study was 66 companies. The sampling method in this study used the purposive sampling method, so that a research sample of 18 Primary Consumer companies listed on the Indonesia Stock Exchange in 2017-2021 was obtained. The data source used in this study is secondary data. Data analysis was performed using Eviews 10. Partial intellectual capital and dividend policy have no effect on the company's performance, Asset growth affects company performance, the audit committee as a moderation variable can moderate the effect of asset growth relationships on company performance, but cannot moderate intellectual capital relationships on company performance, as well as dividend policy on company performance.